Bioaugmentation with syntrophic volatile fatty acids-oxidizing consortia to alleviate the ammonia inhibition in continuously anaerobic digestion of municipal sludge. (February 2022) - Li, Mao-Ting; Rao, Ling; Wang, Lu; Gou, Min; Sun, Zhao-Yong; Xia, Zi-Yuan; Song, Wen-Feng; Tang, Yue-Qin
Abstract: Ammonia inhibition easily affects the performance of anaerobic digestion (AD) for municipal sludge and the oxidization of volatile fatty acids (VFAs) is the rate-limiting step of this process. Bioaugmentation is considered to be an effective method to alleviate ammonia inhibition of AD, but most study used the hydrogenotrophic methanogens as the bioaugmentation culture. In this study, bioaugmentation of mesophilic AD (MAD) and thermophilic AD (TAD) under ammonia inhibition with syntrophic acetate and propionate oxidizing consortia was investigated. The results showed that the bioaugmented reactors recovered earlier than control reactors with 20 (MAD) and 8 (TAD) days, respectively. The high-throughput 16S rRNA gene sequencing indicated that the relative abundance of carbohydrates fermenter ( Lentimicrobium ), syntrophic VFAs-oxidizing bacteria ( Rikenellaceae_ DMER64, Smithella and Syntrophobacter ) and acetoclastic and hydrogenotrophic methanogens ( Methanosaeta, Methanolinea and Methanospirillum ) increased in MAD after bioaugmentation. However, part of the bioaugmentation culture could not adapt to the high free ammonia (FAN) concentration in MAD and the effect was weakened. In TAD, proteolytic bacteria ( Keratinibaculum and Tepidimicrobium ), syntrophic VFAs-oxidizing bacteria ( Syntrophomonas ) and hydrogenotrophic methanogen ( Methanosarcina ) were strengthened. The effect of bioaugmentation in TAD was durable even at higher organic loading rate (OLR), due to its positive influence on microbial community. These results suggested that the different bioaugmentation mechanism occurred in MAD and TAD, which are derived from the synergetic effects of ammonia tolerance and microbial interactions. Our study revealed the VFAs-oxidizing consortia as bioaugmented culture could be the potential strategy to alleviate the ammonia stress of AD. Graphical abstract: Image 1 Highlights: Bioaugmentation recovered MAD and TAD performance from the ammonia inhibition. Bioaugmentation increased the robustness of thermophilic community at higher OLR. Enrichment of hydrolysis, syntrophic VFAs-oxidation and methanogenesis is crucial. The bioaugmentation mechanisms were different between MAD and TAD. Syntrophic VFAs-oxidizing consortia was effective as the bioaugmented culture.